IMPROVED CHARACTERISTICS OF GLIBENCLAMIDE AS TRANSETHOSOME VESICULAR SYSTEM: PHYSICOCHEMICAL, SOLUBILITY AND IN VITRO PERMEATION STUDY - YUSUF, NURUL ARFIYANTI; ABDASSAH, MARLINE; SOPYAN, IYAN; MAULUDIN, RACHMAT; JONI, I. MADE; CHAERUNISAA, ANIS YOHANA (International Journal of Applied Pharmaceutics, 2024)
Objective: Transethosome as a vesicular system offers high skin permeation; therefore, it is expected to improve the solubility and permeability of the poorly soluble drug glibenclamide. The study aimed to optimize the effect of lipid and surfactant concentration as well as sonication time on the physical characteristics of glibenclamide-loaded transethosomes. Methods: The transethosomes were prepared by solvent evaporation method. An experimental Box-Behnken design optimized the formula by assessing particle size, polydispersity index, zeta potential, and entrapment efficiency as response parameters. Further characterizations were conducted by determining the morphology by TEM, chemical interaction by FTIR, thermal behavior by DSC, as well as solubility improvement by using in vitro drug release and permeation study. Results: The result showed that the optimal formula was that with the lipid composition of 75 mg of soya lecithin, 5 mg of tween 80 as surfactant at a sonication time of 18.79 min. The responses were particle size of 166.8±5.3 nm, polydispersity index of 0.463±0.1, zeta potential of-44.7±2.2 mV, and entrapment efficiency as much as 87.18±3.8%. Glibenclamide-loaded transethosomes exhibited a spherical morphology with no visible aggregation. FTIR study revealed no chemical interactions between Glibenclamide and the excipients. Solubility and in vitro drug release tests showed a significant increase of Glibenclamide from transethosome (p<0.05) compared with that as a bulk powder. Conclusion: Overall, the optimized glibenclamide-loaded transethosomes designed with Box Behnken resulted in improved physicochemical characteristics and increased solubility and drug release compared with that from ethosomes and bulk powder comparison, which will be promising for Glibenclamide to be formulated as transdermal drug delivery.